Novel antibacterial agent prepared by poly (hexamethylene guanidine hydrochloride) functionalized hollow nano-silica - ZHANG Zi-wen; ZHANG Kang-min; YANG Jian-jun; WU Qing-yun; WU Ming-yuan; ZHANG Jian-an; LIU Jiu-yi (Cailiao gongcheng, 2019)
A simple synthetic method of poly(hexamethylene guanidine hydrochloride) grafted hollow nano-silica (HSN-PHMG), a novel antibacterial material, was proposed. The water dispersibility and antibacterial property of HSN grafting of PHMG were improved. The hollow structure of nano-silica was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis were used to characterize the successful grafting of PHMG and the mass fraction of PHMG is about 9.5% in HSN-PHMG. Antibacterial test using Escherichia coil (E.coil) and Staphylococcus aureus (S.aureus) as test strains and the results show that the minimum inhibitory concentration (MIC) of HSN-PHMG on E.coil and S.aureus are all 32 mg/L; E.coil can be completely killed within 2 h when the concentration of HSN-PHMG is 64 mg/L.